Effects of Casein Hydrolysate Prepared with Savinase on the Quality of Bread Made by Frozen Dough - Bekiroglu, Hatice; Ozulku, Gorkem; Sagdic, Osman (Mdpi, 2023)
The effect of casein savinase hydrolysate (CSH) usage on frozen dough (1%, 1.5% and 2%, g/100 g flour) was investigated in terms of rheological, thermal and structural characteristics of wheat doughs and the textural and color properties of corresponding breads. Rheological measurements showed that CSH addition into dough led to a reduction in G ' and G '' values, but a similar trend was not observed in frozen dough samples. The increase in protein band intensity was observed for control dough (CD) after frozen storage (-30 degrees C, 28 days), while there were no increases in the band intensities of the doughs with CSH. The freezable water content of unfrozen doughs decreased gradually with the addition of CSH, dependent on concentration level. Frozen storage caused a notable reduction in the alpha-helices structure of the CD sample (p < 0.05) while no significant variation was observed for the doughs containing CSH (p > 0.05). The lowest specific volume reduction and hardness increment were observed for the breads containing 1.5% and 2% CSH. Frozen storage caused a significant reduction in the b* value of bread crust (p < 0.05), while no significant effect was observed for L* and a* value during frozen storage (p > 0.05). Overall, CSH incorporation into frozen dough can be an alternative that could reduce the quality deterioration of frozen bread.
Keywords: casein hydrolysate; frozen dough; bread quality